PENDAMPINGAN KWT SEKAR MAWAR DALAM PEMANFAATAN LIMBAH TAHU MENJADI NATA DE SOYA DAN TEMPE GEMBUS PENCEGAH OBESITAS - Desti Ambar Wati (Poltekkes Kemenkes Riau, 2026)
The prevalence of adult obesity in Indonesia continues to increase, reaching 23.4% according to the 2023 Indonesian Health Survey. This condition is closely related to low dietary fiber intake and changes in dietary patterns. Meanwhile, Wiyono Village produces large amounts of solid and liquid tofu waste that remain underutilized. This community service program aimed to improve the knowledge and skills of the Sekar Mawar Women Farmers Group (KWT) in processing tofu waste into Tempe Gembus and Nata de Soya as healthy food innovations for obesity prevention. The program applied the Participatory Action Learning System (PALS) through nutrition education using the GEMSOYA E-Booklet, combined with fermentation training and innovative food processing practices. A total of 19 KWT members participated in the activities. The evaluation results showed an increase in the average knowledge score from 74.7 in the pre-test to 83.6 in the post-test. Participants were also able to independently process Tempe Gembus and Nata de Soya using simple household equipment. This program contributes to improving nutrition literacy, promoting the utilization of local food resources within a circular economy framework, and creating opportunities for community-based entrepreneurship to support obesity prevention efforts.